Substantiality and Causality. - Szatkowski, Miroslaw (Philosophische Analyse / Philosophical Analysis., 2014)
This book addresses contemporary problems on substantiality and causality. After presenting rival approaches to substantiality and causality-¬a traditional, ontological view vs. a transcendental one-it presents studies of substance as showing causal aspects and of causality, showing its reference to the category of substance. The last section contains studies of extension as a conceptual background of both substantiality and causality.